في الحيوانات المختبرية Vibrio choleraدراسة تأثير السمي لانزيم البروتييز المنقى من عزلة محلية لبكتريا - نادر, محمد ابراهيم (Al-Nahrain Journal of Science, 2009)
This study revealed the toxic effects of protease enzymes that purified from local isolates Vibrio cholera bacteria, injection of 0.250 mg of enzymes into Rabbit ear vein lead to hair loss, necrosis and bleeding at site of injection. However, protease has visible effects on the heart muscle ranging from necrosis,swelling ,loss of striation and visible engorgement of blood vessels .Whereas mouse lung tissue suffered from obvious thickening concurrently with vascular engorgement .Virtually liver tissue shows random cellular distribution around blood vessels with loss of intact hexagonal arrangement followed by exudation with prominent protein layers that separate between adjacent cells.